2012
DOI: 10.1155/2012/251543
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Configurations for the Use of Smart Dampers with Bracings in Tall Buildings

Abstract: This paper presents wind-induced response reduction in a very slender building using smart dampers with proposed bracingslever mechanism system. The building presents a case study of an engineered design that is instructive. The paper shows that shear response and flexural response of tall buildings present two very different cases for vibration suppression. Smart dampers are implemented optimally in the building to reduce its response in the lateral directions for both structural safety and occupant comfort c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In recent years magnetorheological (MR) dampers have been verified with the unique ability to create the resisting force following the change of various characteristics. In Aly et al [65,66], MR dampers are placed in the tower as an alternative to TMDs and ATMD to reduce the wind-induced responses. The challenge in using such devices in tall buildings is related to where to put the device in the building.…”
Section: Magnetorheological Fluid Dampersmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years magnetorheological (MR) dampers have been verified with the unique ability to create the resisting force following the change of various characteristics. In Aly et al [65,66], MR dampers are placed in the tower as an alternative to TMDs and ATMD to reduce the wind-induced responses. The challenge in using such devices in tall buildings is related to where to put the device in the building.…”
Section: Magnetorheological Fluid Dampersmentioning
confidence: 99%
“…The benefits of using dampers in tall buildings under wind loads are discussed in Hart and Jain [67]. Magnetorheological dampers were used to reduce the acceleration and the design loads of the tower in the two lateral directions ( [65,66], see Figure 20). The authors are currently investigating proper techniques that can be used for mitigation under multihazard loading brought by both wind and earthquakes.…”
Section: Magnetorheological Fluid Dampersmentioning
confidence: 99%
“…To improve the structural behavior some active or passive mass dumpers solutions could be considered [6,[54][55][56]. In the present case, a solution represented by TMD is taken into account.…”
Section: Installation Of Dampersmentioning
confidence: 99%
“…The research results indicated that the use of torsion springs in rotational friction dampers is more effective in improving the seismic performance of structures than traditional dampers. Ribakov et al [16][17][18] studied different forms of the inclined brace lever damping system and proposed an optimal design program to realize the design of the lever damping system, demonstrating that this system possessed a good control effect on the inter-story displacement of the structure through numerical simulation. Combining a lever amplification device with a viscous damping wall, He et al [19,20] conducted model and vibration table experiments, revealing that this new amplification viscous damping wall had a significant energy dissipation ability.…”
Section: Introductionmentioning
confidence: 99%